Developing Entrepreneurship Skills among SMK PK Surabaya Students through a Digital Entrepreneurship Mindset Workshop - Angelica Mutiara Anjani; Celine Margaretha Susanto; Cynthia Yohanna Kartikasari; Olivia Tanaya (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2026)
The Workshop on Developing a Digital Entrepreneurship Mindset aims to enhance the entrepreneurial skills of SMK PK Surabaya students through training sessions and business simulations. This program is designed to equip students with practical skills, such as market analysis, marketing strategies, and business proposal submission. The workshop used a Participatory Action Research (PAR) approach and comprised enrichment sessions and business simulations focused on the Student Entrepreneurship Creativity Program (PKM-K). Pre-test and post-test assessments were used to measure students’ understanding of key business concepts, such as market analysis, proposal writing, and registration procedures. However, a notable gap exists in students’ awareness of the Business Identification Number (NIB) as a legal prerequisite for business establishment in Indonesia. This underlines the lack of NIB socialization, which could hinder the establishment of formal businesses. The conclusion of this study emphasizes the need for the integration of business legality materials in entrepreneurship training, as well as the enhancement of business regulation socialization to encourage the growth of registered businesses in Indonesia.